Investigation Of Work Burnout In Child Labor By 2022 - Ayu Lestary; Makharajani Majid; Herlina Muin (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2022)
Background: Children should be protected and their rights considered, but in fact, the family or the state have not been able to fulfill it. This is a concern because not a few of them work without any restrictions. The family who causes them to work, the family hopes that working children can ease the burden on the family to pay for household needs. This violates the applicable regulations and will have a negative impact on the lives of child workers. Objectives: The purpose of this paper study was to analyze the effect of working time, body mass index and personal hygiene on fatigue to child workers at the Lakessi Central Market, Parepare City. Research Metodes: This type of research is quantitative research was an observational survey method with a cross sectional study design. Results: The results showed that there was an effect legth of work and body mass index on work at Lakessi Sentral Market, Parepare City with p-values of 0.012 and 0.020 (p <0.05) while there was no effect of Personal Hygiene on work fatigue in child laborers at Lakessi Central Market, Parepare City with a p-value 0.188 (p > 0.05). Conclusion: The results showed that there was an effect legth of work and body mass index on work at Lakessi Sentral Market, Parepare City, while there was no effect of Personal Hygiene on work fatigue in child laborers at Lakessi Central Market, Parepare City.